2012
DOI: 10.5194/isprsarchives-xxxix-b1-435-2012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Large-Scale Solar Power Plant by Using Images Acquired by Non-Metric Digital Camera on Board Uav

Abstract: Commission I, ICWG I/VKEY WORDS: Measurement, Non-Metric, Camera, Calibration, Orientation, Application, Engineering, Experiment ABSTRACT:This paper reports an experiment conducted in order to investigate the feasibility of the deformation measurement of a large-scale solar power plant on reclaimed land by using images acquired by a non-metric digital camera on board a micro unmanned aerial vehicle (UAV). It is required that a root mean squares of errors (RMSE) in height measurement should be less than 26 mm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…From the results of the analysis we confirmed the conclusion of our previous paper (Matsuoka et al, 2012) that the deformation measurement of a large-scale solar power plant on reclaimed land by UAV photogrammetry would be feasible if points utilized in orientation of images have a sufficient number of bundles in good geometry.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…From the results of the analysis we confirmed the conclusion of our previous paper (Matsuoka et al, 2012) that the deformation measurement of a large-scale solar power plant on reclaimed land by UAV photogrammetry would be feasible if points utilized in orientation of images have a sufficient number of bundles in good geometry.…”
Section: Resultssupporting
confidence: 83%
“…It was required that a RMSE in height measurement should be less than 26 mm that is 1/3 of the critical limit 78 mm of deformation off the plane of a solar panel. Our previous paper (Matsuoka et al, 2012) reported the initial results of the experiment. Two teams engaged in the experiment at first.…”
Section: Introductionmentioning
confidence: 99%
“…Inasmuch as static or moderately dynamic scenes are considered, many low cost contributions have been reported. [25][26][27][28] However, to the author's best knowledge, there are no records of using low-cost solutions apt to observe highly dynamic phenomena.…”
Section: Related Workmentioning
confidence: 99%
“…Repeated sampling can be used to identify changes in land structure (Carvajal et al 2011;Niethammer et al 2011;Rau et al 2011) such as water erosion, sand accumulation, or land subsidence. A specific example involves Japanese solar farms, which are often built on reclaimed land and therefore subject to reduced efficiency if that land subsides (Matsuoka et al 2012).…”
Section: Visible Light (Rgb)mentioning
confidence: 99%